2005
DOI: 10.1038/sj.tpj.6500340
|View full text |Cite
|
Sign up to set email alerts
|

Response to fluoxetine and serotonin 1A receptor (C-1019G) polymorphism in Taiwan Chinese major depressive disorder

Abstract: Serotonin systems appear to play a key role in the pathogenesis of major depression and the therapeutic mechanisms of antidepressants. The firing rate of dorsal raphe serotonergic neurons is controlled by somatodendritic 5-hydroxytryptamine 1A (HTR1A) autoreceptors, and desensitization of these receptors is implicated in the antidepressant mechanism of selective serotonin reuptake inhibitors. We tested whether a functional polymorphism (C-1019G) in the promoter region of the HTR1A gene and serotonin-related ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(107 citation statements)
references
References 38 publications
6
99
0
Order By: Relevance
“…Hardy-Weinberg equilibrium was examined in studies where genotype frequencies were included. 9,[15][16][17][18][19][20][21][22][23][24][25] Given the lack of unequivocal data for 5-HTTLPR genotype pooling, we tested both dominant and recessive hypotheses: l/l versus l/s-s/s and l/l-l/s versus s/s. Outcome was defined with three phenotypes: remission rate, response rate, and response rate within 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Hardy-Weinberg equilibrium was examined in studies where genotype frequencies were included. 9,[15][16][17][18][19][20][21][22][23][24][25] Given the lack of unequivocal data for 5-HTTLPR genotype pooling, we tested both dominant and recessive hypotheses: l/l versus l/s-s/s and l/l-l/s versus s/s. Outcome was defined with three phenotypes: remission rate, response rate, and response rate within 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Although not covering the locus systematically, several previous studies have provided suggestive evidence for an involvement of other HTR2A variants in antidepressant outcome (Minov et al, 2001;Cusin et al, 2002;Peters et al, 2004;Choi et al, 2005;Hong et al, 2006;Kato et al, 2006;McMahon et al, 2006;Paddock et al, 2007;Perlis et al, 2009). Post-mortem (McKeith et al, 1987Lopez-Figueroa et al, 2004) and positron emission tomography (PET) (Yates et al, 1990;Yatham et al, 2000;Mintun et al, 2004) studies have reported both increased and decreased HTR2A receptor number and binding in different brain regions of depressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…6 In contrast to these findings, the majority of previous studies investigating the inheritance of 5-HTTLPR genotype on antidepressant efficacy have found the short allele to be associated with reduced antidepressant response. [7][8][9][10][11][12][13][14][15][16] This may be explained by a number of variables that differ between the studies. First, variation in the criteria used to measure response has differed between studies, with a reduction of 50% or more from baseline Hamilton Depression Rating Scale (HAMD) scores used in certain studies, 4,5,7,13,[15][16][17] but an HAMD score of 8 or less was used to determine response in other studies.…”
Section: Discussionmentioning
confidence: 99%